2018
DOI: 10.1039/c7ta08885j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing at intermediate temperature on oxygen transport kinetics of Pr2NiO4+δ

Abstract: Decomposition of the layered Ruddlesden–Popper (RP) phase Pr2NiO4+δ into higher order phases during long-term annealing dramatically enhances oxygen transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…Oxygen incorporation directly on LSF in the active state shows the same temperature dependency as when this process is facilitated by Pr2Ni1-xCuxO4 decorations. Saher et al [74] and Sadykov et al [79] also observed Arrhenius-type kchem temperature dependencies in Pr2NiO4 samples, with activation energies of ~1 and ~0.9 eV respectively, which is also in-line with the measurements in this study.…”
Section: Ecrsupporting
confidence: 92%
See 1 more Smart Citation
“…Oxygen incorporation directly on LSF in the active state shows the same temperature dependency as when this process is facilitated by Pr2Ni1-xCuxO4 decorations. Saher et al [74] and Sadykov et al [79] also observed Arrhenius-type kchem temperature dependencies in Pr2NiO4 samples, with activation energies of ~1 and ~0.9 eV respectively, which is also in-line with the measurements in this study.…”
Section: Ecrsupporting
confidence: 92%
“…This indicates that atomic oxygen in some form is involved in the rate-determining step (RDS) of the overall oxygen reduction reaction [52,[68][69][70]. The fact that the n-value is not equal to 0.5 but lower, could indicate that some other species, which increase in concentration with reducing pO2, such as oxygen vacancies in the oxides (LSF), are also involved in the RDS [38,[71][72][73][74][75][76][77][78]. The low reaction order points to that the incorporation process of atomic species (possibly ionized) into the material is the slowest step in overall oxygen reduction reaction.…”
mentioning
confidence: 99%
“…20 SOFCs with cathode materials of La 2 NiO 4+d and Nd 2 NiO 4+d show no degradation in cell performance aer hundreds of hours of operation at 750-800 C. 21,22 Pr 2 NiO 4+d , on the other hand, starts to decompose upon annealing in air above 580 C to a mixture consisting of Pr 4 Ni 3 O 10Àd , PrNiO 3Àd and Pr 6 O 11 . [23][24][25][26][27][28][29][30][31] Though apparent oxygen diffusion and surface exchange kinetics are enhanced aer thermal decomposition, 23 a signicant degradation of cell performance is observed for the SOFC with Pr 2 NiO 4+d as the cathode aer 1000 h of operation at 750 C. 22 Meanwhile, there is a growing interest in using higher order RP nickelates as the cathode material. Among the n ¼ 2 members, Ln 3 Ni 3 O 7Àd (Ln ¼ La, Pr, Nd), so far only La 3 Ni 2 O 7Àd could be prepared in a phase-pure form, while Pr 3 Ni 2 O 7Àd and Nd 3 Ni 2 O 7Àd have been observed only as disordered intergrowths in the corresponding n ¼ 3 members.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that research on the Ruddlesden-Popper series oxides continues to attract the interest of the research community and although self-diffusion is well characterised theoretically and experimentally, the focus is on proton diffusivity, doping and structural/electronic/magnetic properties [126][127][128][129][130][131][132][133][134][135].…”
Section: Ruddlesden-popper Layered Oxidesmentioning
confidence: 99%